2017
DOI: 10.1007/s00240-017-0979-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome contributes to renal injury mediated by hyperoxaluria in a murine model of nephrolithiasis

Abstract: Metabolic syndrome (MS) individuals have a higher risk of developing chronic kidney disease through unclear pathogenic mechanisms. MS has been also related with higher nephrolithiasis prevalence. To establish the influence of MS on renal function, we designed a murine model of combined metabolic syndrome and hyperoxaluria. Four groups of male Sprague-Dawley rats were established: (1) control group (n = 10) fed with standard chow; (2) stone former group (SF) (n = 10) fed with standard chow plus 0.75% ethylene g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Detectable inflammatory serum markers have been reported in renal stone patients [10], and in diabetic patients with urolithiasis compared to diabetic patients without urolithiasis [22]; the latter supports our recent findings that metabolic disease exacerbates local kidney inflammatory reaction in a rat model of hyperoxaluria [23]. Other studies, however, did not find any significant differences in serum values of inflammatory markers amongst four groups of patients: control, metabolic syndrome, urolithiasis, or both [24], similar to the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Detectable inflammatory serum markers have been reported in renal stone patients [10], and in diabetic patients with urolithiasis compared to diabetic patients without urolithiasis [22]; the latter supports our recent findings that metabolic disease exacerbates local kidney inflammatory reaction in a rat model of hyperoxaluria [23]. Other studies, however, did not find any significant differences in serum values of inflammatory markers amongst four groups of patients: control, metabolic syndrome, urolithiasis, or both [24], similar to the present study.…”
Section: Discussionsupporting
confidence: 92%
“…However, the relationship between inflammation and potential oxidative stress was not analyzed. Moreover, the 65 days of treatment with a 60% fructose diet in their study did not successfully induce MS features other than dyslipidaemia, and thus, their model should not be recognized as a successful MS rat model [ 18 ]. Our previous studies [ 19 , 20 ] also indicated that MS could be induced in ob/ob mice fed normal chow at 28 weeks of age.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoxaluria model has recently been characterized by our group in previous studies [ 9 , 10 ]. This model develops kidney failure with a significantly lower creatinine clearance compared to the control group, higher percentage of tubules affected by crystal deposits, and interstitial inflammation of the animals affected.…”
Section: Methodsmentioning
confidence: 99%
“…This model develops kidney failure with a significantly lower creatinine clearance compared to the control group, higher percentage of tubules affected by crystal deposits, and interstitial inflammation of the animals affected. Levels of oxaluria were also higher in the OX group [ 9 , 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation